Guidance for clinicians and patients with non-small cell lung cancer in the time of precision medicine - Villaruz, Liza C.; Socinski, Mark A.; Weiss, Jared (Frontiers in Oncology, 2023)
Major advances in the diagnosis and treatment of non-small cell lung cancer (NSCLC) have resulted in a sharp decline in associated mortality rates, thereby propelling NSCLC to the forefront of precision medicine. Current guidelines for recommend upfront comprehensive molecular testing for all known and actionable driver alterations/biomarkers (EGFR, ALK, ROS1, BRAF, KRAS, NTRK, MET, RET, HER2 [ERBB2], and PD-L1), especially in advanced disease stages, as they significantly influence response to therapy. In particular, hybrid capture-based next-generation sequencing (HC-NGS) with an RNA fusion panel to detect gene fusions is a veritable requirement at both diagnosis and progression (resistance) of any-stage non-squamous adenocarcinoma NSCLCs. This testing modality ensures selection of the most timely, appropriate, and personalized treatment, maximization of therapeutic efficacy, and prevention of use of suboptimal/contraindicated therapy. As a complement to clinical testing and treatment, patient, family, and caregiver education is also key to early screening and diagnosis, access to care, coping strategies, positive outcomes, and survival. The advent of social media and increased internet access has amplified the volume of educational and support resources, consequently changing the dynamics of patient care. This review provides guidance on integration of comprehensive genomic testing with an RNA fusion panel as a global diagnostic standard for all adenocarcinoma NSCLC disease stages and provides key information on patient and caregiver education and resources.